QRCODE BASED BATIK PRODUCT LABELING INNOVATION AS A STRENGTHENING OF PERSONAL BRANDING AND INCREASING THE MARKETING OF BATIK MSMEs AS COMPETITION PREPAREDNESS IN THE GLOBAL MARKET - Sunarjo, Wenti Ayu; Muhardono, Ari; Edi Wibowo, Dwi; Maghfiroh, Maghfiroh (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This community service activity is important to carry out because there is an urgency to introduce batik products more widely, especially Pekalongan batik which has its own distinctive and unique motifs and philosophies, and has differentiation which will be packaged through batik innovation with Quick Response Code labeling which can be accessed by consumers with a display that contains information about the profile of the SME maker along with the batik motifs complete with meanings and symbols and philosophies. Through this strategy, SMEs can market batik products more exclusively but still maintain the local wisdom and philosophy of Indonesian batik culture. In addition, SMEs are also able to boost the independence of SMEs in readiness for competition in the global market. The activity was carried out with partners, namely the Kauman Batik Kampoeng Association, East Pekalongan District, Pekalongan City. Activity partners have problems in the commercialization of branding and digital marketing. The method is carried out through several stages. Before the service team carries out activities, it begins with observations, adjusting the needs of service activity partners and creating a website for information needs that can be accessed via QRcode-based labels. The service team provides solutions to problems through training and assistance, including regarding the importance of QRCode-based batik labels, preparing UKM profiles for the QRCode database which refers to the website, assistance in using QRCode-based batik labels, as well as assistance and management of brand rights and copyrights.